Pendidikan Akhlak Bermasyarakat Dalam Perspektif Hadis Nabi - Rohmansyah, Rohmansyah (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2017)
This research aims to describe and provide concrete explanations about how the Prophet Muhammad provide moral education in hanging out and wrestle in public life. The community consists of a human community composed of, among others, children, father, mother, grandmother and others who have a wide range of different characteristics. Based on the research method of library reseach and descriptive data collection methods-intepretatif, generate a conclusion about the words of the Prophet which is very simple yet important and relevant to be applied in the life of society. As the Prophet of the settlement solution is to teach moral education among other noble; First, drop by and receive the guests. Second, establish good relations with the neighbours namely mutual say greetings and respond when encountering each other, looked out the person being sick, complementary invitation if not hitch, delivering bodies came to the liang lahat and answer the person who sneezes. In addition, the education of morals who delivered Prophet is the third, building a social piety to his fellow man. Fourth, establish ukhuwah islamiyah with fellow human beings. The fourth point when developed in the life of a nation and a country then it will create a social life that is dignified and appropriate grain berkeadaban pancasila first until the fifth sila. Therefore, values morals education of society who delivered Prophet Muhammad in his sayings provide an inspiration and motivation to keep doing tajdÃÂ«d (renewal) of good character at the center of public life. Moral education of community implies to all existence of Islam in all his teaching either can the Quran nor Hadith the Prophet, either about the creed, worship and muamalah as political, economic and others.ÃÂ In addition, forming a disciplined man, leading to emotional intelligence and spiritual, wise, brave, keep yourself and be fair.